Identifying causes of variability in outcomes in children with acute lymphoblastic leukemia treated in a resource‐rich developing country. Issue 6 (31st December 2014) - Jastaniah, Wasil; Elimam, Naglla; Abdalla, Khalid; Iqbal, Basheer Ahmed Cittana; Khattab, Taha M.; Felimban, Sami; Abrar, Mohammed Burhan
<x xml:space="preserve">Abstract</x> Background The outcome of children with acute lymphoblastic leukemia (ALL) in developing countries is less favorable than in developed countries, primarily due to resource constraints. However, it is unknown whether the therapeutic results differ. Thus, we hypothesized that outcomes in resource‐rich developing countries would be similar to those in industrialized regions. Procedure We performed a retrospective analysis of 224 consecutive children with ALL, who were treated according to the Children's Cancer Group (CCG) protocols between January 2001 and December 2007. High‐risk (HR) and standard‐risk (SR) patients were treated with modified CCG‐1961 and CCG‐1991 protocols, respectively. Modifications included substitution of dexamethasone for prednisone in HR patients and addition of two intrathecal methotrexate treatments for CNS2 patients during induction. All patients received double delayed intensification with two interim maintenance phases. Results Five‐year overall survival (OS), event‐free survival (EFS) and disease‐free survival (DFS) were 84.7 ± 2.4%, 77.0 ± 2.9%, and 81.4 ± 2.7%, respectively. Remission was achieved in 98.1% of the patients. Induction failure and relapse rates were 1.9% and 15.1%, respectively. Death as the first event occurred in 6.4% of cases, of which 2.7% and 3.7% involved deaths in induction and remission, respectively. Interestingly, a significant reduction in induction deaths was observed over time. Conclusions Despite the encouraging results observed in the present study, our patients displayed significantly lower survival outcomes compared to subjects treated in major clinical trials conducted by leading leukemia cooperative groups. Furthermore, this work underscores the need for targeted interventions to reduce death as the first event in developing regions. Pediatr Blood Cancer 2015;62:945–950. © 2014 Wiley Periodicals, Inc.